Deciphering the functional mechanism of zinc ions of PARP1 binding with single strand breaks and double strand breaks. Issue 30 (29th June 2022) - Sun, Shuya; Wang, Xin; Lin, Rongfeng; Wang, Kai
Abstract : Poly(ADP-ribose)polymerase 1 (PARP1) is a key target for treatment of cancer-related diseases. Detailed structural changes DBD in PARP1 during the binding process with DNA were investigated and the dynamic conformational differences of DBD caused by zinc ions were revealed. Abstract : Poly(ADP-ribose)polymerase 1 (PARP1) is a key target for the treatment of cancer-related diseases, and plays an important role in biological processes such as DNA repair, regulating a variety of metabolic and signal transduction processes. Understanding the dynamic binding mechanisms between each domain of PARP1 and DNA is of great significance to deepen the understanding on the function of PARP1 and to facilitate the design of inhibitors. Herein, strategies such as classical molecular dynamics simulation, conformational analysis, binding free energy calculation and energy decomposition were used to shed light on the binding mechanisms of different DNA binding domains (DBDs, including ZnF1, ZnF2 and ZnF3) in PARP1 with DNA and on the influences of zinc ions on the binding process. On one hand, during binding with DNA, ZnF2 tends to expand its space to identify the DNA damage sites and ZnF1/ZnF2 recognizes the interfaces on both sides of DNA damage rather than one side during the process of DNA repair. More importantly, the stable secondary structure of L 2 of ZnF2 (PRO146 to MET153) is the key conformational change for ZnF1 and ZnF2 to recognize DNA damage. Meanwhile, ZnF3 has little effect on the binding mechanisms of PARP1. On the other hand, for the structural differences of DBD domains, zinc ions in ZnF1 and ZnF2 (Zn1 and Zn2) have an impact not only on the conformational changes of PARP1, but also on the conformational changes brought by the interaction of double strand breaks (DSB) and single strand breaks (SSB). And meanwhile, Zn3 also has little effect on ZnF3 for the system of ZnF3/DSB. The findings presented in this work deepen the understanding on the functional mechanism of PARP1 and provide a theoretical basis for further study on the interaction between different inhibitors and DBD domains to design more potential inhibitors.